Skala Kesantunan Berbahasa Dalam Reels Di Akun Instagram Helobagas : Kajian Pragmatik - Annisa, Zam; Sugiarti, Dewi Herlina; Rosalina, Sinta (Jurnal Ilmiah Wahana Pendidikan, 2024)
It is a descriptive qualitative study. The data found in this study is speech on the scale of language civility, on reels in the helobagas instagram account. The source of the data in this study is the video of reels on the instagram account of helobagas from March 2023 to June 2023. The date-collecting technique by actively reviewing capable libat (SLBC) by listening and then recording the comments found in reels' videos on the helobagas instagram account. Eight data found that match the civility scale according to leech. The fulfillment of the linguistic scale is dominated by a social distance scale, with six data, in which it appears that the mention of the first person's pronoun address (I) with the second person (You) seems to be relaxing because of having a social distance close to the other person. Meeting the scale of loss and gain as much as one data, that is, the scale of the benefits acquired by the person of speech, is the prayer uttered by speakers as' me 'and' me 'persons who are lost in grief because of not being able to forget the character' you. ' The scale of impermanence has been found as much as one data, where it has been found that speech that implies that no one wants a farewell from the other person, the 'you'. No fulfillment on the scale of choice and authoritativeness.